CD47 functions as a removal marker on aged erythrocytes. (31st May 2013) - van, R.
<x xml:space="preserve">Abstract</x> CD47 on erythrocytes inhibits phagocytosis through interaction with the inhibitory immunoreceptor signal regulatory protein alpha (SIRPα) expressed by macrophages. Thus, the CD47‐SIRPα interaction constitutes a negative signal for erythrocyte phagocytosis. However, we recently reported that CD47 does not only function as a 'don't eat me' signal for uptake but can also act as an 'eat me' signal. In particular, a subset of old erythrocytes present in whole blood was shown to bind and to be phagocytosed via CD47‐ SIRPα interactions. Furthermore, we provide evidence that experimental ageing of erythrocytes induces a conformational change in CD47 that switches the molecule from an inhibitory signal into an activating one. We also demonstrate that aged erythrocytes have the capacity to bind the CD47‐binding partner thrombospondin‐1 (TSP‐1) and that treatment of aged erythrocytes with a TSP‐1‐derived peptide enabled their phagocytosis by human red pulp macrophages. Finally, CD47 on erythrocytes that had been stored for prolonged time was shown to undergo a conformational change and bind TSP‐1. These findings reveal a more complex role for CD47‐ SIRPα interactions in erythrocyte removal, with CD47 acting as a molecular switch for controlling erythrocyte phagocytosis.